2016
DOI: 10.1021/acs.chemrestox.6b00146
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Biphenyls Induce Oxidative DNA Adducts in Female Sprague–Dawley Rats

Abstract: Polychlorinated biphenyls (PCBs) are organic chemicals that were traditionally produced and widely used in industry as mixtures and are presently formed as byproducts of pigment and dye manufacturing. They are known to persist and bioaccumulate in the environment. Some have been shown to induce liver cancer in rodents. Although the mechanism of the toxicity of PCBs is unknown, it has been shown that they increase oxidative stress, including lipid peroxidation. We hypothesized that oxidative stress-induced DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…ROS/RNS are obviously involved in the molecular damage that precedes a mutation and cancer initiation. While it is well substantiated that reactive species directly attack and damage the genome, other partially reduced species, e.g., hydroxynonenal, a product of lipid peroxidation, also has carcinogenic potential [ 114 ]. Thus, any agent or process that limits their formation or quickly neutralizes ROS/RNS would likewise lessen cancer incidence.…”
Section: Cancer Initiation: Genomic Damage and Instabilitymentioning
confidence: 99%
“…ROS/RNS are obviously involved in the molecular damage that precedes a mutation and cancer initiation. While it is well substantiated that reactive species directly attack and damage the genome, other partially reduced species, e.g., hydroxynonenal, a product of lipid peroxidation, also has carcinogenic potential [ 114 ]. Thus, any agent or process that limits their formation or quickly neutralizes ROS/RNS would likewise lessen cancer incidence.…”
Section: Cancer Initiation: Genomic Damage and Instabilitymentioning
confidence: 99%
“…Current data strongly point to PCBs induction of liver, lung, bladder, breast and prostate cancer expansion in rodents and humans (Di Lorenzo et al 2015 ; Hashmi et al 2016 ; Mutlu et al 2016 ; Parada et al 2016 ; Pi et al 2016 ). Other accumulating epidemiological evidence of elevated tumor risk and mortality in individuals exposed to PCBs led to their recent classification as a human carcinogen by the International Agency for Research on Cancer (IARC 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the endometrial adenocarcinoma Ishikawa cells, PCBs affected the expression of inflammatory factors through estrogen receptors (ERs) and the aryl hydrocarbon receptor (AhR), with no adverse effects on estrogen metabolism (Chen et al 2015 ). In the rodent male reproductive system, exposure to PCBs decreased serum testosterone and changed the function of the lutropin receptor and activity of both steroidogenic and antioxidant enzymes (Murugesan et al 2009 ). In testes of mice treated with PCBs, the estradiol level was decreased, while expressions of ERβ and ERα were increased (Cai et al 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…60 Female Sprague–Dawley rats were treated with 3,3′,4,4′,5-pentachlorobiphenyl (PCB 126), 2,2′,4,4′,5,5′-hexachlorobiphenyl (PCB 153), and a binary mixture (PCB 126 + 153) for 14, 31, and 53 weeks, respectively. 60 Multiple oxidatively induced DNA lesions (8-oxo-dG, ε dA, N 2 ,3- ε dG, 1, N 2 - ε dG, M 1 dG, Acr-dG, Cro-dG, and HNE-dG, Figure 1) were enriched from the enzymatic digestion mixture of DNA using offline HPLC and quantified by LC-MS/MS. It was revealed that the levels of these DNA lesions were significantly elevated after treatment with PCBs, especially in groups treated with the binary mixture for 53 weeks.…”
Section: Recent Developments In Lc-ms-based Analysis Of Dna Adductsmentioning
confidence: 99%
“…It was revealed that the levels of these DNA lesions were significantly elevated after treatment with PCBs, especially in groups treated with the binary mixture for 53 weeks. 60 A similar sample preparation strategy was employed for simultaneous quantifications of etheno-DNA adducts in human white blood cells, 61 as well as tissues of LEA and LEC rats. 55 Li et al 61 reported an ultrasensitive UPLC-ESI-MS/MS method for the analyses of ε dA and ε dC in white blood cells of human subjects with occupational exposure to benzene.…”
Section: Recent Developments In Lc-ms-based Analysis Of Dna Adductsmentioning
confidence: 99%